Presence of selected metabolic syndrome components in patients with psoriasis vulgaris - Uczniak, Sebastian; Gerlicz, Zofia A.; Kozłowska, Magdalena; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: Recent studies have suggested a strong association between psoriasis and obesity, dyslipidemia, hypertension, resistance to insulin and metabolic syndrome. Aim : To assess the prevalence of selected metabolic syndrome components in patients with psoriasis and the effect of the abnormalities on the disease activity. Material and methods: Two hundred and forty-six patients diagnosed with psoriasis and 75 healthy individuals as controls were included in the study. Psoriasis activity was evaluated by the Psoriasis Area and Severity Index (PASI). Results : There was a statistically significant difference in triglyceride concentration between psoriasis patients and controls (p = 0.00001), which was not found for high-density lipoprotein (HDL) concentration. Mean values of serum glucose level in patients with psoriasis were significantly higher than in controls (p = 0.046). Further statistical analysis of the obtained results showed significantly higher systolic blood pressure in the psoriasis patients than in the controls (p = 0.0001), but there was no statistically significant difference in diastolic blood pressure between the investigated groups (p > 0.05). Conclusions : Higher prevalence of metabolic syndrome components was observed in patients with psoriasis than in the general population.